Air quality co-benefits for human health and agriculture counterbalance costs to meet Paris Agreement pledges. Issue 1 (December 2018) - Vandyck, Toon; Keramidas, Kimon; Kitous, Alban; Spadaro, Joseph; Van Dingenen, Rita; Holland, Mike; Saveyn, Bert
Abstract Local air quality co-benefits can provide complementary support for ambitious climate action and can enable progress on related Sustainable Development Goals. Here we show that the transformation of the energy system implied by the emission reduction pledges brought forward in the context of the Paris Agreement on climate change (Nationally Determined Contributions or NDCs) substantially reduces local air pollution across the globe. The NDCs could avoid between 71 and 99 thousand premature deaths annually in 2030 compared to a reference case, depending on the stringency of direct air pollution controls. A more ambitious 2 °C-compatible pathway raises the number of avoided premature deaths from air pollution to 178–346 thousand annually in 2030, and up to 0.7–1.5 million in the year 2050. Air quality co-benefits on morbidity, mortality, and agriculture could globally offset the costs of climate policy. An integrated policy perspective is needed to maximise benefits for climate and health. Local air quality co-benefits can provide convincing support for climate action. Here the authors revisited air quality co-benefits of climate action in the context of NDCs and found that 71–99 thousand premature deaths can be avoided each year by 2030, offsetting the climate mitigation costs on a global level.